Calibration procedure for a laser triangulation scanner with uncertainty evaluation. (November 2016) - Genta, Gianfranco; Minetola, Paolo; Barbato, Giulio
Abstract: Most of low cost 3D scanning devices that are nowadays available on the market are sold without a user calibration procedure to correct measurement errors related to changes in environmental conditions. In addition, there is no specific international standard defining a procedure to check the performance of a 3D scanner along time. This paper aims at detailing a thorough methodology to calibrate a 3D scanner and assess its measurement uncertainty. The proposed procedure is based on the use of a reference ball plate and applied to a triangulation laser scanner. Experimental results show that the metrological performance of the instrument can be greatly improved by the application of the calibration procedure that corrects systematic errors and reduces the device's measurement uncertainty. Highlights: Most of low cost 3D scanning devices are sold without a user calibration procedure. No standard procedures exist for checking the performance of a 3D scanner along time. A method to calibrate a 3D scanner and assess its measurement uncertainty is defined. The procedure uses a reference ball plate and is applied to a laser scanner. Experimental results show that metrological performances of the scanner are improved.